Reflexivity in Applied Linguistics Research in the Tourism Workplace. (26th March 2020) - Sharma, Bal Krishna
Abstract: Linguistic ethnographers largely agree that engaging in self-reflexivity enables researchers to identify how their actions, subjectivities, and motivations influence research. In this article, I argue for a discourse-oriented ethnographic account as an alternative method for documenting and reporting such reflexivity. The overall goal of this article is to examine reflexive research practices in the study of tourism communication. Presenting illustrative cases, I closely analyze how the researcher's co-presence naturally opens up opportunities for some form of intervention in tourist–guide dyads. I show that researcher participation that is intended to resolve local interactional problems can have unintended consequences resulting in marginalization or exclusion of the key participants. The analysis shows that the researcher is not only the knowledge-maker in applied linguistics research but is also an object of analysis in the process. Overall, the study is intended to invite workplace researchers to reflect on whether and how much to participate, how their participation shapes researcher–participant relationships, how their relationship impacts data and knowledge claims, and how issues of balance and distance can be negotiated.